FIFA 11+ Kids program effects on jump kinetics in soccer players - A randomized controlled clinical trial - Teixeira, V. A.; Queiroz, T. M.; Leão, I. V.; Innecco, L. D. G.; Marcelino, E. L.; Lobato, D. F. M. (Research in Sports Medicine, 2023)
This study aimed to analyse the effects of the FIFA 11+ Kids programme on jump kinetics in soccer players. Twenty-four athletes (aged 9-11 years) were randomly allocated to the following groups: 1) the FIFA 11+ Kids programme (FT, n = 12), and 2) control training (CT, n = 12). Kinetic assessments of vertical jump (VJ), drop landing (DL), and anterior jump + maximum vertical jump (AJ) were performed on a force platform before and after eight weeks of training. Post-intervention impulse peak force and maximum impulse force (VJ) were significantly greater than the baseline values in the FT group (P < 0.001). Post-intervention landing peak force values for the first and second landings (DL) were significantly greater than the baseline values in the FT group (P = 0.01 and P = 0.05, respectively). Post-intervention landing peak force in the first landing (AJ) was significantly greater than the baseline values in the FT group (P = 0.005). The FT was effective in improving the impulsion performance during VJ. However, it increased the landing forces during DL and VJ.